Human Ecology Economics (HEE) and Strategic Management - Allen, R.; Hosie, Peter; Herkenhoff, L. (Centre for Promoting Ideas, 2015)
Human Ecology Economics (HEE) draws on evolutionary and complex systems processes by incorporating interdisciplinary material from the humanities and sciences. Lessons for strategic managers follow from this HEE perspective with examples from the banking industry. HEE can nurture a broad environmental perspective among strategic managers and an ontological understanding of their organization within its dynamic ecology. Reconciliation is attempted between the chaotic dualities inherent in strategic management (SM).